Phase I study of dose‐escalated stereotactic body radiation therapy for locally advanced pancreatic head cancers: Initial clinical results. (18th August 2021) - Qing, Shuiwang; Gu, Lei; Zhang, Huojun
Abstract: Purpose: To establish the maximum tolerated dose (MTD) of stereotactic body radiation therapy (SBRT) for locally advanced pancreatic head cancers. Methods: A total of 16 patients were included in the single‐institution phase I dose‐escalation study. The initial dose level was 35 Gy in five fractions, doses were then sequentially escalated to 37.5 Gy, 40 Gy, 42.5 Gy, and 45 Gy. The dose‐limiting toxicity (DLT) was defined as III/IV GI (gastrointestinal) toxicity. Results: A total of 16 patients with locally advanced pancreatic head cancers were analyzed, 14 patients had received gemcitabine or S1‐based chemotherapy. Median OS and LPFS were 14.5 months and 12.5 months, respectively; The OS rates at 1 and 2 years were 68.8% and 25%, respectively. No grade 3 or 4 acute or late GI toxicities were observed. Grade 3 toxicities were observed in four patients with three hematologic toxicities and one biliary obstruction for acute toxicities, G1–2 of GI late toxicity were in 31.25% of patients. Conclusions: SBRT doses ranging from 35 to 45 Gy in five fractions could be given for patients with locally advanced pancreatic head cancers without severe GI toxicities, whereas the side effect of biliary obstruction should be paid more attention. Trial registration: Clinical trials:NCT02716207. Abstract : This is the first study for dose escalating of SBRT in pancreas head cancers.This research showed SBRT doses ranging from 35 to 45 Gy in five fractions could be given for patients with locally advanced pancreatic head cancers without severe GI toxicities, whereas the side effect of biliary obstruction should be paid more attention.